THE SIGNIFICATION OF DEATH STORYLINE IN TEENLIT REFLECTED IN “LOOKING FOR ALASKA” BY JOHN GREEN - Tomi Arianto (Asosiasi dosen IDEBAHASA KEPRI, 2022)
Literary works often include the theme of death as part of the story. But it is seldom realized that the theme of death gave a very significant role to the storyline. It is undeniable that the author deliberately put the theme of death as the core issue to convey something behind the story. This article discussed the sociological study of literature related to the representation of death in contemporary literary works. A teen lit novel by John Green entitled Looking for Alaska is the source of the data in this article. This article limits the research by referring toward two problem formulations; first, how the representation of death can be expressed in the novel. Second, how the theme of death in the novel is related to the social phenomenon of American society, in this case related to the modern society view towards death. The researcher used Hagin's theory regarding the significance of death in literary works. The method used is descriptive qualitative. The results of the study indicated that the theme of death has a significant role in the story where the death is present in the middle of the story or it is categorized as an intermediate of death (in Hagin concept). Death becomes meaningful in relation to the present, events that are still happening and have not been completed. Using Hagin's perspective, the role of death in Looking for Alaska is categorized into three; the manner of establishing the goal, obstacles, and the forming of death. Meanwhile, the relationship between death and the perspective of modern society is explored using Aries concept in the term Forbiden of Death. Death is considered a thing to be feared, so everyone tries to deny, reject, and stay away from death. Death is visualization for everyone who is haunted by emptiness, an emptiness that blinds vision and creates the fear.